Upaya Guru Al-Qur'an Hadits dalam Meningkatkan Kemampuan Baca Al-Qur'an Peserta Didik MA Balongrejo Sumobito Jombang - Abdul Natsir; Abdul Rouf; Muhtadi Muhtadi (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2022)
This study is to find the efforts of Al-Qur'an Hadith teachers in improving the reading skills of the students of MA Balongrejo Sumobito Jombang. This research is a qualitative research that uses a psychological and pedagogical approach. The data sources are: primary data and secondary data. The instruments used in data collection are: observation, interviews and documentation. Analysis of the data used is data processed by qualitative analysis by going through the stages of data reduction, data presentation, and verification. The results showed that the supporting factors of Al-Qur'an Hadith teachers in improving the ability to read the Qur'an were, the existence of extracurricular activities of tahfidz Qur'an and adequate facilities and infrastructure. As for the factors that become obstacles, namely, there are still students who have not been able to read the Qur'an, and the efforts of Al-Qur'an Hadith teachers in improving the ability to read the Qur'an, namely, providing motivation, taking approaches, habituation of tadarrus Al -The Qur'an to students at every hour of the Al-Qur'an Hadith lesson begins, and gives assignments / homework in the form of memorizing surahs related to the material discussed at each meeting.